Peripheral inflammatory markers in amnestic mild cognitive impairment. (15th July 2013) - Karim, Salman; Hopkins, Steve; Purandare, Nitin; Crowther, Jackie; Morris, Julie; Tyrrell, Pippa; Burns, Alistair
<x xml:space="preserve">Abstract</x> Objective To prospectively monitor plasma inflammatory marker concentrations in peripheral blood, over 12 months, in subjects with amnestic mild cognitive impairment (MCI), and to determine the relationship between peripheral inflammatory markers and cognitive decline. Methods Seventy patients with amnestic MCI were recruited from two sites providing specialist memory assessment services in Manchester. The baseline assessment included physical examination, neuro‐psychological testing and venous blood samples for C‐reactive protein (CRP) and interleukin 6 (IL‐6) concentrations. Sixty two participants were followed up after 12 months and the assessments were repeated. Results Data analysis revealed a significant rise in CRP, but not IL‐6 concentrations over 12 months, which was not confounded by demographic variables. The neuro‐psychological test scores had no association with CRP or IL‐6 concentrations at baseline or 12 months follow‐up. Conclusion This study adopted the unique approach of prospectively investigating peripheral inflammatory markers in a cohort with amnestic MCI. A significant rise in CRP concentrations over 12 months, but lack of significant association with cognition, provide no evidence for a relationship between systemic inflammation and cognitive decline in amnestic MCI. © 2013 The Authors. International Journal of Geriatric Psychiatry published by John Wiley & Sons, Ltd.